Dampak Stres Pekerjaan pada Produktivitas Staf Hotel Pekanbaru - Rizkia Nasta; Hendrayani Hendrayani (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research was conducted at Hotel XYZ which is located at Jl. Yos Sudarso No. 12-A. The purpose of this study was to determine the effect of discipline on employee performance at Hotel XYZ. In analyzing the data obtained, the research object used descriptive and quantitative analysis. The number of samples taken by researchers was 30 respondents, to obtain maximum processed data, research data were processed using the SPSS 23. 0 program. Based on the discussion with simple linear regression, the resulting regression equation is: Y = 6. 553 + 0.859 X, constant (a) of = 6.553 and the value of the regression coefficient (b) = 0.859 stating that the work stress variable (X) is considered constant, then performance employee (Y) is 0.859, meaning that if work stress increases by 1 unit, then performance will increase by 0.859, if the value of work stress increases, the value of performance increases. The value of tcount (15.953) is greater than the value of ttable (2,000324) with a significance level of 0.000 <0.05, so it can be concluded that work stress has a positive and significant effect on employee performance at Hotel XYZ. The R2 value is 82.0% while the remaining 19.0% is influenced by other variables that are ignored or not examined in this study.